Desenvolvimento infantil e condições de saúde de lactentes de risco com perda de seguimento em unidade de referência - Tiago Simoes Leite (2018)
Introduction: One of the greatest challenges in comprehensive healthcare nowadays is to increase the adhesion to follow-up programs, especially in vulnerable populations. Long term follow-up in children increases survival rates, prevents disease occurrence and improves global development. It is important to offer a qualified, caring and multi professional assistance, strengthening the bond between health professionals and families and thus, lowering absenteeism and evasion rates. Furthermore, it is necessary to identify reasons behind abandoning the follow-up and develop tools to rescue and evaluate the absent patients. Objective: Evaluate development and health conditions in vulnerable infants after drop-out of follow-up in a reference health service. Methods: We conducted a retrospective cohort based on telephone interviews with the parents of children that dropped out their follow-up at Sofia Feldman Hospitals reference clinic. Of the 504 infants that began their follow-up between 2015 and 2016, 283 dropped out before reaching 2 years of age. Of this sample, we interviewed 105 parents. We used a structured form to evaluate the childrens health conditions for the past 12 months and the reasons behind abandoning the follow-up. The Survey of Wellbeing of Young Children (SWYC) was applied to evaluate family risk factors and neuropsycomotor and behavioural development. The socioeconomic classification was done using the ABEPs Brazilian Criteria. We conducted a comprehensive analysis of the sample, describing health and developmental problems. To evaluate which factors were associated with SWYC results, we adjusted the sample in a logical regression and adopted a level of 5% as statistically relevant. Results: We successfully contacted about 43% of the drop-out families via telephone calls. Family profile showed 23% of teenage mothers and an average of formal education of 9.85+2.47 years. Using Brazilian criteria, 78.2% were part of C/D/E classes. Only 13.5% had government financial aid. 87.6% of the infants in this sample had at least one episode of sickness in a one-year period, but only 14.3% where admitted to hospital care during that period. The more prevalent reasons for dropping out the reference clinics follow-up were distance from the clinic (51.4%) followed by financial difficulties (22.9%). Of the drop out infant sample, 98.1% had a follow-up program in another health care service, 86.4% of those where consulted by paediatricians (with or without other health professionals) and 71.8% attended the consults in a public primary care clinic. Almost 52% had 5 or more consults in a 12-month period. As for the global development, we found a prevalence of 27.6% at risk for developmental impairment, 41% at risk for behavioural problems and 30% at risk for developing Autism Spectrum Disorder (ASD). We found an association between parents concerns about their childrens development, learning or behaviour and the occurrence of abnormal SWYC results in those three areas. That means a 3-6 times higher risk for development and behavioural impairment and ASD. Conclusion: The global evasion rate was like shown in literature. The infants on this studys sample showed good vital signs when they were born and a low rate of perinatal complications, but the majority were under environmental risk for developmental impairment by being part of families of low income, low formal education and with a high prevalence of teenage mothers. The follow-up program instituted after the reference clinic drop out in the studied population was considered adequate in terms of healthcare, thus providing and appropriate place of follow-up, frequency and type of health visits. This study showed developmental and behavioural impairment risks similar to those in the literature. The data found regarding ASD risk was higher than that found in the literature. We found an association between parents concerns about their childrens development, learning or behaviour and increased risk for problems in development, behaviour and ASD.